Women's football in Oceania - McGowan, Lee (Lecturer in creative writing), author.
1 online resource.
Keywords: "This book presents the most comprehensive mapping and analysis of women's football in Oceania and is the first to examine the game's historical development alongside social, political and cultural issues, weaving origin stories with players' day-to-day challenges. Women's Football in Oceania covers key events, actors and moments and fills a gap in research for scholars of sports history and women's history"--